A analysis of passenger facilitation at Terminal 1, Kuala Lumpur International Airport Subang / Saiful Nizam Mohamed - Mohamed, Saiful Nizam (Faculty of Business and Management, 1990)
In the name of Allah, the most Benevolent and Merciful. It is prominent that Terminal 1, Kuala Lumpur International Airport, Subang which handles the international passenger, has been receiving an increasing' number- of passenger annually. This terminal, in meeting its main objective and function as a passenger terminal is equipped with various facilities for passenger handling. The DCA as the airport authority is responsible to ensure that the terminal's services meet the international requirement and reach a sufficient level of passenger facilitation. The annual passenger growth makes the DCA's job becomes tougher due to more problems arise. The purpose of this study is mainly to analyse the passenger facilitation at Terminal 1, Subang Airport and whether it is adequate, in the context of maintaining the sufficient level of passenger handling system. For this purpose, research will be made on two aspects; the Queing Pattern and the Terminal Space Requirement. As the guidelines in determining the service level, various Planning Standards will be adopted. Earlier, the passenger movement will be studied to determine the peak pattern, where most of the problems arise. Every aspect of facilitation concerning the departing, arriving and transit passenger will be analysed especially regarding passenger formalities processing. At the end of the study, recommended solutions will be discussed for solving the problems as well as to improve the passenger handling system.